HOUSE DUST MITE ALLERGY IN VIEW OF MOLECULAR ALLERGOLOGY - E. S. Korovkina (SPb RAACI, 2014)
Abstract. Incidence of allergic diseases is increased over last years. House dust is considered a major risk factor of allergic sensitization which plays an important role in development of allergic rhinitis, bronchial asthma, atopic dermatitis. Dust mites in the home comprise a large part of domestic allergens. Dermatophagoides pteronyssinus, Dermatophagoides farinae, Euroglyphus maynei, Lepidoglyphus destructor, Blomia tropicalis are most important in this respect. Der p 1 and Der p 2 are regarded as major house dust mite allergens. Recent studies concerned induction of IgE responses against mite tropomyosin (Der p 10), an allergen occurring in mites which exhibits high cross-reactivity with tropomyosins from a variety of sea foods (e.g. shrimps), as well as human tropomyosins. Allergen-specific immunotherapy (ASIT) represents the only causative approach to allergy treatment in such cases. From this viewpoint, a quantitation of specific IgЕ against major house dust mite allergens would be necessary to predict ASIT efficiency. Treatment by house dust mites allergen extracts is effective in management of allergic rhinitis and mild asthma. A component-resolved diagnostic (CRD) with purified house-dust mites allergens allows to discriminate patients who were mostly sensitized to the major house dust mites allergens (e.g. Der p 10, tropomyosin). The component-resolved diagnostics could be performed before starting the allergen-specific immunotherapy by mite allergens, in order to avoid unresponsiveness to this mode of therapy.